The Urgency of Strengthening Character Education in Elementary Schools Through Local Wisdom in the Industrial Revolution Era 4.0 - Ilham Mubarok; Isman Noer Rahmatulloh (International Consortium of Education and Culture Research Studies, 2020)
This study discusses the importance of strengthening character education for elementary school children through local wisdom in the era of the industrial revolution. In the era of the industrial revolution 4.0 Character education is an important aspect to develop the affective domain of children. Its content is applied in learning in primary schools based on material from the curriculum content standard. Elementary school children are now more individualistic, difficult to get along with and prefer to play gadgets rather than playing with their peers. Therefore, the teacher can utilize and develop local wisdom-based material that contains a lot of views and rules so that children have more foothold in determining an action in their daily activities. Local wisdom has a close relationship with traditional culture in an area. In an effort to cultivate local wisdom, teachers can utilize technology that is developing rapidly in the current era. In order for students to know and be able to take the values ​​contained in the local wisdom. The research method uses literature study which uses data analysis based on published written material.